JA’FAR AL-ṢĀDIQ DAN PARADIGMA HUKUM MAZHAB JA’FARI - Dani Muhtada (Al-Ahkam, 2015)
This article explores the legal paradigm of the Ja’fari school of law. The article presents the profile of Imam Ja’far, the founder of this school of law. It also discusses some legal thoughts presented by the Ja’fari school of law, which seemed to be fundamentally different from the legal thoughts of the Sunni school of law (e.g., khumus and mut’ah). This article concludes that the legal sources used in the Ja’fari school of law are not fundamentally different from those used in the Sunni school of  law, which include the Quran, the Sunnah, Ijma, and reasoning. Although there might be different approaches among the Ja’fari school of law and the Sunni school of laws in defining these legal sources, this article indicates no principle difference in legal making procedure. As a matter of fact, the differences in the legal making process could also exist among the Sunni school of laws.